Aortic valve endocarditis due to Bartonella clarridgeiae in a dog in Brazil - André,Marcos Rogério (2019)
Abstract We report the first documented case of endocarditis associated with Bartonella clarridgeiae in a dog in Latin America. Infective vegetative valvular aortic endocarditis was diagnosed in a 10-year-old male mixed breed dog. The dog presented grade V/VI systolic and diastolic murmur, hyperthermia, and progressive weight loss. Cardiomegaly and presence of diffuse alveolar pattern in the lung fields were observed in the thorax radiography evaluation. Irregular and hyperechogenic structures adhered to the aortic leaflets, causing obstruction of the left ventricular outflow tract and severe aortic insufficiency, were observed in the echocardiography evaluation. A vegetative, whitish, hardened structure measuring 1.0 cm in diameter was observed in aortic semilunar valve at necropsy. Based on a combination of pre-enrichment insect-based medium liquid culture, quantitative real-time and conventional PCR assays based on nuoG and gltA genes, respectively, followed by sequencing and phylogenetic inferences, B. clarridgeiae DNA was detected in the patient’s aortic valve lesions. Clinical, echocardiographic, anatomopathologic and molecular features supported the diagnosis of severe aortic vegetative endocarditis possibly caused by B. clarridgeiae in a dog in Brazil.